Effect of 2 Psychotherapies on Depression and Disease Activity in Pediatric Crohn's Disease. Issue 6 (June 2015) - Szigethy, Eva; Youk, Ada O.; Gonzalez-Heydrich, Joseph; Bujoreanu, Simona I.; Weisz, John; Fairclough, Diane; Ducharme, Peter; Jones, Neil; Lotrich, Francis; Keljo, David; Srinath, Arvind; Bousvaros, Athos; et al.
Abstract : Background: Crohn's disease (CD) is associated with depression. It is unclear if psychosocial interventions offer benefit for depressive symptoms during active CD. In this secondary analysis of a larger study of treating depression in pediatric inflammatory bowel disease, we assessed whether cognitive behavioral therapy (CBT) would differentiate from supportive nondirective therapy in treating depression and disease activity in youth with CD. We also explored whether somatic depressive symptoms showed a different pattern of response in the overall sample and the subset with active inflammatory bowel disease. Methods: Youth with depression and CD (n = 161) were randomized to 3 months of CBT (teaching coping skills) or supportive nondirective therapy (supportive listening). Depressive severity was measured using the Children's Depression Rating Scale-Revised (CDRS-R) with the somatic depressive subtype consisting of those CDRS-R items, which significantly correlated with CD activity. Disease activity was measured by the Pediatric Crohn's disease Activity Index. Given the potential confound of higher dose steroids, subanalyses excluded subjects on >20 mg/d prednisone equivalent (n = 34). Results: Total CDRS-R scores in the overall sample significantly decreased over time after both treatments ( P < 0.0001). Treatment with CBT was associated with a significantly greater improvement in the Pediatric Crohn's disease Activity Index ( P = 0.05) and somatic depressive subtype ( P = 0.03) in those with active inflammatory bowel disease (n = 95) compared with supportive nondirective therapy. After excluding those on steroids (n = 34), there was a significant improvement in total CDRS-R ( P = 0.03) and in Pediatric Crohn's disease Activity Index ( P = 0.03) after CBT. Conclusions: Psychotherapy may be a useful adjunct to treat depression in the context of CD-related inflammation in youth who are not concurrently on higher dose steroids. Abstract : Article first published online 27 March 2015.